2020
DOI: 10.1371/journal.pntd.0008276
|View full text |Cite
|
Sign up to set email alerts
|

Reservoirs and transmission routes of leprosy; A systematic review

Abstract: Leprosy is a chronic infectious disease caused by Mycobacterium leprae (M. leprae) and the more recently discovered Mycobacterium lepromatosis (M. lepromatosis). The two leprosy bacilli cause similar pathologic conditions. They primarily target the skin and the peripheral nervous system. Currently it is considered a Neglected Tropical Disease, being endemic in specific locations within countries of the Americas, Asia, and Africa, while in Europe it is only rarely reported. The reason for a spatial inequality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
105
0
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(126 citation statements)
references
References 95 publications
1
105
0
20
Order By: Relevance
“…In the narratives of patients, sand (soil) and animals are considered "carriers" of the disease. Meanwhile, modern scientific research has shown that leprosy bacteria can actually survive in the soil and furthermore occur in certain animals in nature [76]. It should come as no surprise that the limited information on this matter from neighboring countries also points in the same direction.…”
Section: Concluding Remarks: a Call For An Ecological Approachmentioning
confidence: 99%
“…In the narratives of patients, sand (soil) and animals are considered "carriers" of the disease. Meanwhile, modern scientific research has shown that leprosy bacteria can actually survive in the soil and furthermore occur in certain animals in nature [76]. It should come as no surprise that the limited information on this matter from neighboring countries also points in the same direction.…”
Section: Concluding Remarks: a Call For An Ecological Approachmentioning
confidence: 99%
“…El Mycobacterium leprae al entrar al organismo es fagocitado y destruido por los polimorfonucleares. En la enfermedad de Hansen el bacilo logra evadir esta barrera defensiva, por lo que es fagocitado por macrófago, el complejo bacilo-macrófago se aloja en la piel, en las mucosas y alrededor de vasos sanguíneos y los nervios (16). En 2020 han surgido nuevos hallazgos en cuanto a la fisiopatología de la enfermedad de Hansen, Cristina et al Indica que existe interferencia entre el metabolismo celular y las respuestas inflamatorias / inmunes y explica cómo estas pueden influir entre sí.…”
Section: Fisiopatologíaunclassified
“…Environmental and zoonotic reservoirs have been described as modes of transmission of infection, however their significance in terms of case numbers is not fully understood. [ 19 ]…”
Section: Introductionmentioning
confidence: 99%